2018
DOI: 10.1002/adsc.201800669
|View full text |Cite
|
Sign up to set email alerts
|

Relay Catalysis of Bismuth Trichloride and Byproduct Hydrogen Bromide Enables the Synthesis of Carbazole and Benzo[α]carbazoles from Indoles and α‐Bromoacetaldehyde Acetals

Abstract: Benzo[a]carbazoles were synthesized from 2-phenylindoles and a-bromoacetaldehyde using bismuth trichloride as a catalyst. The reaction was triggered by a bismuth trichloride-catalyzed Friedel-Crafts alkylation of these two precursors, which provided a tryptaldehyde intermediate that underwent intramolecular olefination to form the final product. Interestingly, the HBr byproduct generated in the upstream step of the reaction catalyzed the following downstream reaction steps, thus creating a byproduct-participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Recently, we have found that, in the presence of a Brønsted acid, tryptaldehyde can act as a 1,4‐donor‐acceptor molecule to react with a β ‐ketoester in the manner of [4+2] annulation to form carbazoles . Inspired by this reactivity, we tried to establish a molecular library of all‐carbon 1,4‐nucleophilic‐electrophile molecules for enriching the product diversity of the third [4+2] annulation model, and make it be practically useful for the construction of fused six‐membered rings.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have found that, in the presence of a Brønsted acid, tryptaldehyde can act as a 1,4‐donor‐acceptor molecule to react with a β ‐ketoester in the manner of [4+2] annulation to form carbazoles . Inspired by this reactivity, we tried to establish a molecular library of all‐carbon 1,4‐nucleophilic‐electrophile molecules for enriching the product diversity of the third [4+2] annulation model, and make it be practically useful for the construction of fused six‐membered rings.…”
Section: Methodsmentioning
confidence: 99%
“…Given the abundance of readily accessible simple indoles and the wide range of commercially available aryl ketones 50 , the suggested catalytic technique is a potential way for the synthesis of carbazole libraries with a high degree of diversity (Scheme 35). 122,123…”
Section: Lewis Acid Catalysed Synthesis Of Polyfunctional Groups Subs...mentioning
confidence: 99%
“…In 2019, the Verma group [1m] reviewed the synthesis of carbazoles from indoles (2015–2019). The Gu group [4a,b] utilized α‐ bromoacetaldehyde acetal as the key reagent in the indole‐mediated benzo[ α ]carbazoles [4b] . During the Bi(OTf) 3 ‐catalyzed three‐component reactions[4a], the Friedel‐Crafts alkylation and hydrolysis generated aldehyde intermediates.…”
Section: Nucleophilic C3mentioning
confidence: 99%